(3GdJfhjQ TQM GdLGeY GdUZjQs - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG HGdCfhGQ GdfHhjI aEf ScJGH GdLGeY GdUZjQ LeY ef GdCMGOjK GdfHhjI GdWjH GdcKjQ s
(3BNQgG (B:s
(3aGFOI , PcQ GdSgjdi Yf GdhGbOi Cf Chd cdeI Jcde HgG GdeUWai Udi Gddg Ydjg hSde LdGd QHi GdQajY hEdi gfG aQZ Qbe GdLRA GdKGdK ef GdJfhjQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHgG HYfGjI GdeDda (B_ (3GHfg ceG hQO ai BNQ GdLRA GdQGHY ef GdfSNI faSgG cJH GdeJf HGdMeQI s
(3CJe GdeDda JCdjag SfI (B1154(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdMOjK h GdeUWdMs